DEVELOPMENT OF STUDENTS’ METHODOLOGICAL COMPETENCE IN TEACHING THE ELECTROMAGNETISM SECTION THROUGH MODERN PEDAGOGICAL APPROACHES AND INNOVATIVE TECHNOLOGIES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Modern pedagogical approaches and innovative educational technologies were applied to develop students’ methodical competence in teaching the Electromagnetism section of physics. An instructional model integrating interactive methods (laboratory work, PhET simulations, problem-based learning, etc.) and individualized learning trajectories was implemented for physics education students. A pedagogical experiment (with experimental and control groups) demonstrated that this approach significantly improves the future teachers’ methodological competence and understanding of electromagnetism. The results confirmed the effectiveness and practical significance of the proposed method in higher education.